PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN ETIKA ANAK SEKOLAH MINGGU DI GPdI KAVLING SEROJA BATAM - Cristiovani Agustina Tarihoran; Gomgom Purba; Maruba Situmorang; Tiani Zai (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The aim of this research is to determine the application of the cooperative learning model to improve the ethics of Sunday school children at GPdI Kavling Seroja Batam. This research is research in the form of field research or field research is a type of research. This research is a qualitative descriptive research. The data in this research comes from primary and secondary data. Data collection methods use observation, interviews and documentation. Interviews were conducted with the community at the PkM location. The research results obtained in implementing cooperative learning to improve the ethics of Sunday school children at GPdI Kavling Seroja Batam mean that a Sunday school teacher can make the ethics of Sunday school children better and learning more active. Using creative learning models is one way that can be done. implemented so that learning becomes more active and will influence the learning outcomes of Sunday school children. This success is determined by other interesting activities that can support the improvement of Sunday school children's soft skills. The inhibiting factor in efforts to maximize this is the lack of understanding of parents regarding this matter, the school environment and the home environment of Sunday school children.